Daya Tarik Enhypen Sebagai Brand Ambassador, Brand Awareness, dan Loyalitas Fandom Terhadap Minat Beli Produk - Zamala, Ajeng Aini; Astanti, Anis Dwi; Adianto, Shochib (Magister Manajemen Universitas Wisnuwardhana, 2026)
This study aims to analyze the effect of Enhypen's attractiveness as a brand ambassador, brand awareness, and fandom loyalty on the purchasing interest of Nabati x Enhypen collaboration products among Enhypen fans in Indonesia. The data used are primary data obtained through the distribution of questionnaires to Enhypen fans in Indonesia. The research method used is a quantitative approach with a purposive sampling technique. The sample size in this study is 105 respondents who meet the research criteria. Data analysis was conducted using multiple linear regression analysis. The results of the study indicate that the attractiveness of the Enhypen brand ambassador does not have a significant effect on purchase intention, while brand awareness and fandom loyalty have a positive and significant effect on purchase intention. Simultaneously, the three independent variables have a significant effect on purchase intention.